Performance of Soluble CD28 and CTLA4 as a Potential Marker of Immunosenescence - Pratama, Mirza Zaka; Handono, Kusworini; Poetri, Levrita Nindya; Maghfirah, Halimi Bidaimi (Clinical and Research Journal in Internal Medicine, 2025)
Background: Immunosenescence is a condition of decreased function of the immune system that is generally found in elderly individuals. Several costimulatory molecules, such as CD28 and CTLA-4 have been investigated for their essential role in the immune aging process. Aim: This study aimed to determine the role of the soluble costimulatory molecules in immunosenescence. Methods: This study was observational research with cross-sectional approach. Samples were tested using ELISA and flow cytometry examination. Statistical analysis was conducted using independent T-test or Kruskal-Wallis comparison test. Correlation between each biomarker was determined with Pearson or Spearman correlation test. Diagnostic performances of each biomarked were assessed using ROC curve. Results: This study involved 52 subjects, of which 20 were young individuals aged between 20 to 28 years and 32 were elderly individuals aged between 60 to 85 years. In this study we found that CD4CD28+ and CD8CD28+ T cells were lower in elderly group (p<0.001), while CD4CD57+ and CD8CD57+ T cells were higher in elderly group (p<0.001). sCD28 and sCTLA-4 were significantly higher (p 0.039 and p 0.025 respectively) in old individuals than in young individuals. CD8CD28+ and sCD28 exhibit a significant negative moderate correlation (p=0.007, r= -0.368) meanwhile sctla4 has no correlation with surface immunosenescence markers. Based on the results of roc analysis, sCTLA-4 was the best predictor to determine immunosenescence with area under curve of 0.7. The cut-off value for sCTLA-4 to determine immunosenescence is 26.5 ng/ml with sensitivity and specificity 58.6% and 63.2% respectively. Conclusion: sCTLA-4 as a soluble costimulatory molecule can be developed as promising predictive biomarkers of immunosenescence, which could be detected more quickly and efficiently using elisa as an alternative to flowcytometry.